The High Calcium, High Phosphorus Rescue Diet Is Not Suitable to Prevent Secondary Hyperparathyroidism in Vitamin D Receptor Deficient Mice - Grundmann, Sarah M.; Brandsch, Corinna; Rottstädt, Daniela; Kühne, Hagen; Stangl, Gabriele I. (Frontiers in Physiology, 2017)
The vitamin D receptor (VDR) knockout (KO) mouse is a common model to unravel novel metabolic functions of vitamin D. It is recommended to feed these mice a high calcium (2%), high phosphorus (1.25%) diet, termed rescue diet (RD) to prevent hypocalcaemia and secondary hyperparathyroidism. First, we characterized the individual response of VDR KO mice to feeding a RD and found that the RD was not capable of normalizing the parathyroid hormone (PTH) concentrations in each VDR KO mouse. In a second study, we aimed to study whether RD with additional 1% and 2% calcium (in total 3% and 4% of the diet) is able to prevent secondary hyperparathyroidism in the VDR KO mice. Wild type (WT) mice and VDR KO mice that received a normal calcium and phosphorus diet (ND) served as controls. Data demonstrated that the RD was no more efficient than the ND in normalizing PTH levels. An excessive dietary calcium concentration of 4% was required to reduce serum PTH concentrations in the VDR KO mice to PTH levels measured in WT mice. This diet, however, resulted in higher concentrations of circulating intact fibroblast growth factor 23 (iFGF23). To conclude, the commonly used RD is not suitable to normalize the serum PTH in VDR KO mice. Extremely high dietary calcium concentrations are necessary to prevent secondary hyperthyroidism in these mice, with the consequence that iFGF23 concentrations are being raised. Considering that PTH and iFGF23 exert numerous VDR independent effects, data obtained from VDR KO mice cannot be attributed solely to vitamin D.